Coordination of O-Propyl-N-phenylthiocarbamate to HgI2 and the Crystallographic Characterization of an Anilinium Chloride Thiocarbamate Adduct - Wafa Arar; Nuri Ekici; Michael Knorr; Isabelle Jourdain; Carsten Strohmann; Jan-Lukas Kirchhoff (Molbank)
In order to investigate the coordination chemistry of O-alkyl N-aryl thiocarbamate ligands, HgI2 was reacted with one equivalent of PrOC(=S)N(H)Ph L in toluene solution to afford the 1D polymeric title compound [{IHg(μ-I)}{κ1-PrOC(=S)N(H)Ph}]n CP1. The formation of this iodide-bridged coordination polymer was ascertained by a single-crystal X-ray diffraction study performed at 100 K, as well as the formation of an adduct between anilinium chloride and L forming a supramolecular ribbon of composition [L(PhNH3)(Cl)]. The occurrence of anilinium chloride is due to the partial hydrolysis of L in the presence of HCl.